Ammonia sensing by closely packed WO3 microspheres with oxygen vacancies. (August 2018) - Wang, Chu-Ya; Zhang, Xing; Rong, Qing; Hou, Nan-Nan; Yu, Han-Qing
Abstract: Ammonia (NH3 ), is a precursor for the formation of atmospheric fine particulate matter (PM2.5 ), and thus establishing efficient and cost-effective methods to detect ammonia emission is highly desired. Transition metal oxide semiconductors-based sensors for electrochemical gas sensing have been extensively explored. Among various types of semiconductors, tungsten oxide (WO3 ) possesses an anisotropic layered crystalline structure and is recognized as a promising material for gas sensing. However, the performance of commercial WO3 is unsatisfactory because of its high impedance and low charge transportation efficiency. Thus, the modification of commercial WO3 is needed to make it an efficient ammonia sensor material. In this work, closely packed WO3 microspheres with oxygen vacancies were synthesized successfully through a novel two-step hydrothermal route. Our WO3 showed a good selectivity to ammonia sensing, and its response intensity was 2.6 times higher than that of commercial WO3 because of its optimized conductivity. Moreover, the mechanism behind its robust ammonia sensing performance was elucidated. The effectiveness of the as-prepared WO3 microspheres for ammonia sensing also suggests a new strategy for modifying transition metal oxide materials. Graphical abstract: Image 1 Highlights: WO3 microspheres were synthesized using commercial WO3 without surfactant. The as-prepared WO3 exhibited a substantial enhancement in ammonia sensing. Mechanism for its robust ammonia sensing performance was elucidated. Potential of the developed sensor for ammonia detection was demonstrated. Abstract : Capsule : An efficient and cost-effective method to detect ammonia emission was developed using the closely packed WO3 microspheres with oxygen vacancies.